Decentralization, public spending, and other structural reforms (2022)
Structural reforms are essential for economic growth and development. This dissertation consists of three chapters in which I explore the new scope of structural reforms and the effect that some of them have on local state capacity. In particular, in the first chapter, I find the impact of public spending on academic performance under different institutional contexts related to administrative decentralization. In the second (with Fabio Sánchez and Jean-Paul Faguet), we explore the effects of decentralization on the historical gaps in the quality and provision of public services and the collection of local taxes. In the third chapter (with Sebastían Bustos, Luis Felipe Céspedes, and John León-Díaz), we present a methodological proposal to identify the areas for reform worldwide and the intensity with which they are discussed.